Kill fore being killed: an experimental approach supports the predator-removal hypothesis as a determinant of intraguild predation in top predators - Rabaça, J.E. (2012)
Intraguild predation (IGP) has been explained in terms of competitor-removal, food-stress and predator removal hypotheses. Only the first two hypotheses have been fairly well studied. To test the predator-removal hypothesis as a force determining IGP in avian predators, we performed a field experiment to simulate the presence of an IG predator (eagle owl Bubo bubo dummy) in the surrounding of the nests of four potential IG prey (black kite Milvus migrans, red kite Milvus milvus, booted eagle Aquila pennata and common buzzard Buteo buteo). To discard the possibility that an aggressive reaction towards the eagle owl was not related to the presence of the IG predator, we also presented a stuffed tawny owl Strix aluco, which is a potential competitor but cannot be considered an IG predator of the studied diurnal raptors considered in the experiment. While almost always ignoring the tawny owl, raptors chiefly showed an interspecific aggressive behaviour towards their IG predator. Our results seem to support the predator-removal hypothesis, as the IG prey may take advantage of the diurnal inactivity of the IG predator to remove it from their territory. However, the recorded behaviour may be also considered as a special variety of mobbing (i.e. a prey’s counter-strategy against its predator), where the mobber is sufficiently powerful to escalate predator harassment into deliberate killing attempts. In their turn, eagle owls can respond with an IG predatory behaviour aimed at removing IG prey species which are highly aggressive mobbers.